Liberating Minds, Strengthening Voices: How Education Transforms Women's Political Empowerment - Umar Daraz; Mohammad Hussain; Zakir Hussain; Abdul Hanan; Ibrahim (Indus Journal of Social Sciences, 2025)
This comprehensive study explores the intricate relationship between education and women's political empowerment in the unique context of Malakand Division, Pakistan. It underscores the transformative power of education in dismantling societal barriers, fostering leadership skills, and promoting civic engagement among women. The research employs a mixed-methods approach, combining qualitative interviews and thematic analysis to provide nuanced insights into the experiences of women aged 18 and above in Malakand Division. The findings reveal that education serves as a catalyst for women's emancipation, enabling them to challenge cultural norms and actively participate in decision-making. Despite identified challenges such as educational disparities, the study emphasizes the need for targeted interventions to ensure equal access and the development of a curriculum that transcends traditional subjects. Education emerges as a gateway to political participation, equipping women with critical thinking skills and knowledge for meaningful engagement in policy discussions. Leadership development through education is highlighted, showcasing the instillation of confidence, communication skills, and a strategic mindset. Civic education is recognized as foundational for political involvement, providing essential knowledge about democratic processes. The study also emphasizes the strategic role of education in planning and executing advocacy campaigns, contributing to impactful policy change. Policy implications include targeted interventions to address educational disparities, curriculum reform emphasizing inclusivity, and strengthening civic education initiatives. Policymakers are urged to invest in leadership development programs for women and encourage community and family support through awareness campaigns and incentives.